2000
DOI: 10.1103/physrevlett.84.47
|View full text |Cite
|
Sign up to set email alerts
|

Coster-Kronig Decay of theAr2sHole Observed by Auger-Threshold Photoelectron Coincidence Spectroscopy

Abstract: The Coster-Kronig lines associated with Ar2s decay have been resolved within the natural linewidth of the 2s hole for the first time. This was possible by a new spectroscopic technique, relying on resonance enhanced double photoionization, Auger-threshold photoelectron coincidence spectroscopy. Contrary to standard Auger spectroscopy, this technique can filter out weak components in Auger spectra corresponding to a well-defined inner-shell state and, furthermore, can achieve a resolution no longer limited by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…In a groundbreaking experiment on gaseous Xe, Viefhaus et al [78] have shown that, by recording the photoelectron and the Auger electron in coincidence it is possible to filter out very weak components in the Auger energy spectra. Further on, at least for stable (dicationic) Auger final states, the achievable energy resolution of the experiment is not limited by the lifetime of the decaying inner-shell hole, as confirmed also by the results of Lablanquie et al [79]. Further on, by this technique one is enabled to measure e.g.…”
Section: Photoelectron -Auger Electron Coincidencesupporting
confidence: 48%
“…In a groundbreaking experiment on gaseous Xe, Viefhaus et al [78] have shown that, by recording the photoelectron and the Auger electron in coincidence it is possible to filter out very weak components in the Auger energy spectra. Further on, at least for stable (dicationic) Auger final states, the achievable energy resolution of the experiment is not limited by the lifetime of the decaying inner-shell hole, as confirmed also by the results of Lablanquie et al [79]. Further on, by this technique one is enabled to measure e.g.…”
Section: Photoelectron -Auger Electron Coincidencesupporting
confidence: 48%
“…Indeed detailed studies have appeared recently since the introduction of electron / electron coincidence techniques in the field 1 . A partial and non exhaustive list of recent electron / electron coincidence experiments includes valence double ionization of atoms 2 and especially of He 3,4 , of molecules 2,5,6 and especially of H 2 , 7,8 and coincidence studies of Auger 9,10,11,12,13,14,15 and double Auger decays 16,17 . However in most of these examples only a small part of all the processes releasing several electrons is explored as most of the studies have restricted their coincidence detection system or the event analysis to processes where exactly 2 electrons are emitted.…”
Section: Introductionmentioning
confidence: 99%
“…If the released particle is detected and its energy measured with an appropriate resolution, the Raman line narrowing is restored [6].…”
Section: Examplesmentioning
confidence: 99%